A Question of Power: Bessie Head and her Publishers. Issue 3 (4th May 2018) - Davis, Caroline
Abstract : This article examines Bessie Head's turbulent relationships with her publishers and literary agents in London and New York, focusing on the publication ofA Question of Power in 1973. It traces her business negotiations carried out from Serowe, in Botswana, and the difficulties she faced in getting the manuscript accepted before it was eventually taken on by Heinemann Educational, Davis-Poynter and Pantheon Books. Based on new archival records, the article analyses the impact of the publishers' interventions in the text and paratexts of the novel, and it assesses her contracts with these publishers and her difficulties in obtaining royalties or remuneration. While her publishers and biographer have attributed her battles with the literary establishment to her volatile nature or to mental illness, this article draws attention instead to the difficulties that Head faced in forging a literary career.